Leptin induces altered differentiation of keratinocytes by inducing insulin resistance: implications for metabolic syndrome-induced resistance of psoriatic therapy - Rui Wang; Chongli Yu; Zijie Tang; Jie Sun; Youlin Wang; Zhenkai Zhao; Biwen Lin; Chengxin Li (Taylor & Francis Group, 2024)
AbstractBackground: Psoriatic patients tend to develop metabolic syndrome (MS). MS accelerates psoriasis, but the exact molecular mechanisms are poorly understood.Objectives: We aim to investigate the impact of leptin on keratinocyte insulin sensitivity and explore its underlying molecular mechanism, which might play a role in the pathogenesis of this disease.Methods: ELISA and immunohistochemistry were applied respectively to detect the level of leptin in serum and in lesion of psoriatic patients with and without MS. The HaCaT cell line was cultured and western-blot assay was performed to assess the change of insulin sensibility. q-PCR and western-blot assay were applied to detect the SOCS3 expressions. Knockdown of SOCS3 were generated in HaCaT cell line by siRNA. Leptin and insulin were treated for 6 days and K10 expression was evaluated by western-blot assay.Results: Patients with MS had higher level of leptin in serum and lesions than their counterparts without MS. Serum levels of leptin was negatively correlated to PASI decline index in psoriatic patients. Long-term treatment of leptin induced insulin resistance in HaCaT cell line, as indicated by elevated expression of p-IRS-1 (ser636) and lower p-PKB (ser473). Leptin treatment up-regulated the mRNA and protein expression of SOCS3. Knockdown of SOCS3 blocked the effect of leptin-induced insulin resistance. Leptin treatment attenuated insulin-elicited K10 expression.Conclusions: Leptin induces insulin resistance by upregulating SOCS3 and give rise to differentiation disorder of keratinocyte. Insulin resistance may serve as a target for anti-psoriatic therapies.